KOMUNIKASI PEMASARAN LURING PONDOK PESANTREN MODERN SAHID DI TENGAH ERA DIGITAL - Sabila Adinda Puri Andarini (Jurnal Penelitian Sosial Ilmu Komunikasi, 2022)
This research discusses marketing communications from Sahid Modern Islamic Boarding School which are run offline by staff and students. The purpose of this study is to find out what kind of offline marketing communication is carried out by Sahid Modern Islamic Boarding School in the current digital era. The method used in this research is descriptive qualitative. Data collection techniques are carried out through interviews and documentation. From the results of the study, it was found that Sahid Modern Islamic Boarding School has implemented several forms of offline promotional activities in attracting prospective students. These offline promotional activities include taking a direct approach to prospective students, such as doing door-to-door strategy, word of mouth, exhibitions, and through business partners. Two-way communication is required, as well as the credibility of the informant and the form of the message are two important points in this research.